The effect of laser shock peening and shot peening on the fatigue performance of aluminium alloy 7075 - Becker, Alexander (Centre for Materials Engineering, 2017)
It has been well established that most fatigue cracks initiate from stress concentration sites found on the surfaces of components subject to cyclic fatigue loading. The introduction of residual compressive stresses into the surface layers of components, through various means including shot peening and laser shock peening, can result in local residual compressive stresses which provide a resistance to both crack initiation and propagation, thus leading to an increase in the fatigue life of the components. The effects of both laser shock peening (LSP) and conventional shot peening (SP) on the fatigue properties of both 7075-T6 and 7075-T0 aluminium round bar test specimens were investigated and compared by means of cyclic 3-point bend fatigue testing. This investigation focused on the role that the peening induced microstructure, surface morphology and hardness had on the fatigue life of the test specimens. It was found that both the laser shock peening and shot peening processes substantially increased the fatigue lives compared to unpeened AA7075-T6. The laser shock peening process more than doubled the fatigue life of the specimens and the shot peening process increased the fatigue life by approximately 1.6×. No discernible hardening effects could be determined in the laser shock peened specimens. However, the shot peening process resulted in a distinct hardened region within the surface layers of the AA7075-T6 specimens which was attributed to the longer pressure duration of the shot peening process which results in greater plastic deformation. It was also shown that polishing the shot peened and laser shock peened specimens after their respective peening procedures resulted in a significant increase in fatigue life. Polishing after peening resulted in a 3.4× fatigue life increase in the shot peened test specimens (T6 condition) and a 5.4× fatigue life increase in the laser shock peened test specimens (T6 condition). This result highlights the role that surface roughness plays in component fatigue life. Furthermore, the increase in the average fatigue life of the polished test specimens shows that the depth of the residual compressive stresses induced by the peening processes were deep enough to allow for surfaces layers to be removed from the test specimens without any detrimental effect to the overall average fatigue life of the components. The result also suggests that the magnitudes of the residual stresses induced by the laser shock peening process being greater than those of the shot peening process. The main difference between the peening treatments was demonstrated as originating from the surface roughening effects of the two peening procedures. The laser shock peening process only slightly increased the surface roughness of a polished AA7075-T6 test specimens. The shot peening process severely affected the surface roughness of the test specimens, creating many potential crack initiation sites. The AA7075-O test specimens (annealed) showed no overall improvement in their fatigue life, regardless of the mechanical treatment received. The increased ductility of the specimens during the 3-point bending fatigue process led to stress relieving of the peening induced compressive stresses. The specimens were however still fatigued to failure. This enabled the analysis of the effect of the peening induced surface roughness to be analysed. It was found that the shot peened and laser shock peened surface roughness values were significantly higher than the roughness values of the T6 specimens owing to the increased ductility and thus workability of the test specimens. These increased surface roughnesses resulted in the shot peened test specimens failing before the laser shock peened specimens. Both sets of peened specimens failed before the "as machined" and polished test specimens highlighting the role that their induced surface roughnesses had on their fatigue lives. The cross-sectional microstructures of the peened samples in each material condition showed varied changes in the microstructure of the treated aluminium alloy. There was evidence of a large degree of plastic deformation near the surface of shot peened specimens in both material conditions. However, there was limited evidence of changes to the grains structure of the laser shock peened specimens, in both material conditions. In addition, the ability of the laser shock peening process to recover fatigue life in damaged components was also investigated. This brought into question whether the laser shock peening process can be used on a partially fatigued component at the point of crack initiation, in an attempt to further improve the fatigue life of the component. It was found that the laser shock peening of the cracks initiated in fatigue life recovery process did little to effectively recover fatigue life in the damaged components. A degree of life extension was present as cracks re-initiated after a few thousand cycles and was attributed to crack tip closure. This closure led to a general reduction in the fatigue crack growth rate when compared to laser shock peened/polished test specimens fatigued at the same stress.